CONTACT FATIGUE LIFE ANALYSIS OF INVOLUTE SPUR GEAR UNDER ELASTOHYDRODYNAMIC LUBRICATION - ZHANG Wei; WU Xing; XIAO ZhengMing; LIU XiaoQin (Jixie qiangdu)
Under the condition of isothermal lubrication taking a involute spur gear as research object,a involute spur gear contact-fatigue life model composed of the lubricated-contact analysis and the explicit analysis was established. The condition which jioned the factor of impact and oil supply was intruduced. Based on the method of multi-grid and multi-grid integration values of pressure and thickness of the film were obtained and substitute the values into explicit analysis. Mises equivalent stress distribution was obtained by explicit analysis and according to Smith-Watson-Topper contact fatigue calculation model,predicting the tooth-contact fatigue life. The result shows that with the increase of the degree of overlap,the danger zone alone the tooth profile closes to the node and the fatigue life also increases. The result also indicates that increasing the degree of overlap can effectively control the impact of the tooth surface contact fatigue life. Compared to full oil state,friction in the contact which lack oil led the fatigue life decreases and the danger zone tends to moved from the subsurface to the surface. The result not only shows the importance of the elastohydrodynamic lubrication in preventing the occurrence of contact fatigue,but also provided a theoretical basis for maching the tooth surface.